Framing analysis of Anies Baswedan as an Indonesian presidential candidate in the sacrificial cow numbered 024 case - Bhakti, Aditya Dwi Putra; Apriliana, Selvia; Nasrullah, Nasrullah (Jurnal Kajian Komunikasi, 2023)
Background: The news coverage from Detik.com and Kompas.com regarding the sacrificial cow numbered 024, associated with Anies as a presidential candidate for 2024, presents an intriguing subject. These media outlets differ in their ideologies. Purpose: This study aims to examine the framing of Anies as a 2024 presidential candidate in the news coverage of Detik.com and Kompas.com during the Eid al-Adha moment in 2022. As each moment during a Political Year holds the potential to influence public opinion and impact the electability of political figures, understanding the framing strategies employed by the media is crucial. Method: This research utilizes a qualitative approach, analyzing ten news articles from Detik.com and two news articles from Kompas.com. The analysis includes an examination of titles, news content, and accompanying pictures or photos, employing Robert Mathew Entman’s framing analysis model. Results: Detik.com and Kompas.com adopt different perspectives in framing the news about Anies. Detik.com presents news in two directions, where some articles suggest that the existence of cow number 024 is merely coincidental, while others imply a connection between the incident and political issues. In contrast, Kompas.com employs a single form of framing, portraying it as a political symbol. Conclusion: It can be concluded that Kompas.com’s coverage is relatively limited and less accommodating compared to Detik.com. However, Kompas.com presents Anies’ reporting as a form of “political language,” positioning him as a potential “dark horse” in the 2024 Indonesian Presidential Election. Implications: This study sheds light on the construction of meaning and public opinion towards Anies, influenced by the news consumed by individuals. The media’s framing of Anies plays a significant role in shaping public perception and impacting public opinion regarding his candidacy.